Optimization of Restorative Justice in the Settlement of Criminal Cases of Fraud and Embezzlement by Police Investigator - Dalimunthe, Surya Wahyu Danil Juni Harsya; Eddy, Triono; Nadirah, Ida (Faculty of Law, Universitas Pekalongan, 2024)
This research discusses the implementation of restorative justice by National Police investigators as a solution to solve criminal cases of fraud and embezzlement of online arisan. The rise of online arisan fraud cases causes material and immaterial losses for the community, as well as adding to the burden on the criminal justice system. The restorative justice approach is an alternative settlement that focuses on recovering victims' losses, accountability of perpetrators, and restoring social relationships. This study uses a mixing method method between normative and juridical by analyzing related legal policies and case studies on the settlement of online arisan fraud cases through a restorative approach. The results of the study show that the implementation of restorative justice is effective in resolving cases quickly, reducing the burden on judicial institutions, and providing a sense of justice and satisfaction for victims and perpetrators. However, challenges such as public legal awareness and consistency in policy implementation still need to be considered. In conclusion, restorative justice is an appropriate and humane solution in dealing with cases of fraud and embezzlement of online social gatherings, provided that there is a commitment from law enforcement officials and clear policy support.